Peroxidase-mediated reaction of the carcinogenic non-aminoazo dye 1-phenylazo-2-hydroxynaphthalene with transfer ribonucleic acid - Stiborová, M; Frei, E; Klokow, K; Wiessler, M; Safarík, L; Anzenbacher, P; Hradec, J (Carcinogenesis, 1990)
Horseradish peroxidase in the presence of hydrogen peroxide has the ability to mediate the activation of carcinogenic 1-phenylazo-2-hydroxynaphthalene (Sudan I) to DNA- and transfer RNA (tRNA)-bound products in vitro. tRNA is more accessible for modification by the activated carcinogen studied. tRNA modified by activated Sudan I becomes colored and has an absorption maximum of approximately 480 nm. Binding of metabolite(s) to tRNA is inhibited by ascorbate, glutathione, Mg2+ ions and nitrosobenzene. The mechanism of these protections was shown to be different for the different agents. tRNA modified by activated Sudan I exhibits a significantly increased acceptance for L-methionine. Enzymatic hydrolysis of modified tRNA with subsequent separation of nucleosides by HPLC suggests that the covalent modification of tRNA originating from the formation of more than one adduct with the nucleosides in tRNA is the predominant interaction of the activated Sudan I with tRNA.
Keywords: Microsomes, Liver; Male; Biotransformation; Rats, Inbred Strains; RNA transferová; radioizotopy uhlíku; naftoly; Hydrogen-Ion Concentration; mužské pohlaví; inbrední kmeny potkanů; Naphthols; Carbon Radioisotopes; koncentrace vodíkových iontů; krysa rodu Rattus; kinetika; Animals; biotransformace; Carcinogens; RNA, Transfer; karcinogeny; zvířata; Rats; Horseradish Peroxidase; DNA; křenová peroxidasa; Kinetics; jaterní mikrozomy